Pengaruh Persepsi Dukungan Organisasi Terhadap Kinerja Karyawan Yang Dimediasi Oleh OCB (Organizational Citizenship Behavior) (Studi pada PT.Angkasa Pura I Kantor Cabang Surabaya) - DWI AGUSTININGRUM, SHERLY (Jurnal Ilmu Manajemen (JIM), 2016)
Perceived organizational support emerged from the support organizations that have been granted by the company to employees. Employees who feel that they are supported by the organization can do best performance than employees who feel a low organizational support. Perceived organizational support can also improve OCB because employees not only tend to develop a sense of duty in the organization but do more outside the obligations they have to do that the results will have an impact on the job performance. This research aimed to examine the impact of perceived organizational support on job performance through organizational citizenship behavior (Studies on PT. Angkasa Pura I Surabaya Branch Office). This type of research is a causality research studies, with the quantitative approach. This research was using 98 respondents saturated sample and collected as many as 97 respondents of PT. Angkasa Pura I Branch Office Surabaya. The statistical analysis used is Structural Equation Modelling (SEM) with analysis method Partial Least Square (PLS). Measurement scale in this research was using likert scale. The results showed that there was a significant direct effect perceived organizational support on organizational citizenship behavior with the value 0.463. There was a significant direct effect organizational citizenship behavior on job performance with the value 0.667. But there was not significant direct effect perceived organizational support on job performance with the value 0.042. OCB mediates the impact of perceived organizational support on job performance. Keywords : Perceived organizational support, Organizational Citizenship Behavior (OCB), Job Performance